Agromyzidae collected in Camonica Valley. Biological and morphological notes, and record of eight species new for Italy. (Bollettino di zoologia agraria e bachicoltura, 2024)
25 species of Agromyzidae have been collected in year 2002; eight species are new for Italy.
Keywords: Agromyzidae; Italy; Val Camonica